Incidencia de las Remesas Sobre el Crecimiento Económico en el Ecuador, período 2000 – 2015 - Zhunaula González., Diana Beatriz (2016)
Remittances sent by emigrants are a monetary income that contributes to the less fortunes homes, therefore this transfers help the countries that collect them. This paper tries to determine if these remittances represent a significant growth or reduction in the economy of the country: under this context it’s have being planned to determine the influence of remittances at Ecuador during the 2000- 2015 period. It is important to mention, that for the development of the subject in particular secondary data coming from different sources such as central bank of Ecuador, National planning and Development secretary, World Bank, National Institute of Development and Statistics was used. This data creates an historical- descriptive and statistical research. In attention to what has being exposed, a general objective has being planted: determine the incidence of the remittances over the economic growth of Ecuador, using an empiric model, period 200-2015. At the same time and Econometric model based on approximation of series of time periods to the Cobb Douglas production function, was designed and constructed, this with the purpose to stablish the incidence of this variables over growth. As a conclusion, once the model was used, it determines that the remittances have a positive influence over the internal gross product, the same occurs with the economic active population and the investment of Capital (Known as control variables) therefore, all of them have significant statistical coefficients.